2014
DOI: 10.1155/2014/128240
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Score Predicting Survival after Palliative Reirradiation

Abstract: Purpose. To develop a prognostic model for predicting survival after palliative reirradiation (PR). Methods and Materials. We analyzed all 87 PR courses administered at a dedicated palliative radiotherapy facility between 20.06.2007 (opening) and 31.12.2009. Uni- and multivariate survival analyses were performed, the previously published survival prediction score (SPS) was evaluated, and a PR-specific prognostic score was calculated. Results. In multivariate analysis, four parameters significantly influenced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The appropriateness of using an arbitrary cut-off to define short survival/end of life (such as the 1 month cut-off used in previous publications) may also be debated, as a number of patients may survive only few days longer than this period (12). In order to avoid administering palliative radiotherapy during the last month of life, or to make informed decisions in cases where patients request treatment, despite limited expectation of survival, a prediction tool was previously developed and validated by Angelo et al (10).…”
Section: Introductionmentioning
confidence: 99%
“…The appropriateness of using an arbitrary cut-off to define short survival/end of life (such as the 1 month cut-off used in previous publications) may also be debated, as a number of patients may survive only few days longer than this period (12). In order to avoid administering palliative radiotherapy during the last month of life, or to make informed decisions in cases where patients request treatment, despite limited expectation of survival, a prediction tool was previously developed and validated by Angelo et al (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the results were not identical. Currently, these patient-reported symptoms are not included in commonly employed prognostic models, e.g., for brain metastasis and lung cancer [ 13 - 15 , 17 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies [ 11 - 12 ], we identified the patients with scores zero for all items (no symptoms), at least one item with score one-two (minimal symptoms), and at least one item with the score three (moderate symptoms). This study was performed to expand our ongoing efforts to develop prognostic models that support the decision making for personalized palliative approaches [ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same was true for the well established SPT-Chow which is generally accepted as a valid survival tool in palliative cancer care [ 20 22 ]. On the other hand, SPT-Nieder which was developed in a small ( n = 87), inhomogeneous patient sample including reirradiations for brain, bone, and lung metastases, as well as primary tumors, among others [ 23 ], showed acceptable predictive separation.…”
Section: Discussionmentioning
confidence: 99%
“…SPT-Chow was chosen because it is a simple and validated tool, widely applicable in palliative settings [ 22 ]. Furthermore, we included the SPT developed for reirradiation in general by Nieder et al [ 23 ]. SPTs as developed by Tokuhashi [ 24 ], Balain [ 25 ], Bauer [ 26 ], Bollen [ 27 ], and Tomita et al [ 28 ], were deemed appropriate.…”
Section: Methodsmentioning
confidence: 99%